QUANTUM DOT SOLAR CELLS: ENHANCING PHOTOVOLTAIC EFFICIENCY THROUGH NANOCRYSTAL SURFACE ENGINEERING - Susatyo Handoko; Karnoto Karnoto (Penelitian dan Pengembangan Ilmu, 2025)
The development of Quantum Dot Solar Cells (QDSCs) is a significant step towards sustainable energy solutions, overcoming the limitations of traditional silicon-based solar cells in terms of efficiency and production cost. This study aims to systematically investigate the effects of nanocrystal surface engineering on charge carrier dynamics and photovoltaic efficiency in QDSCs. Using a systematic literature review (SLR) method, we analyzed peer-reviewed articles published between 2010 and 2024, focusing on surface passivation, ligand exchange, and core-shell structure as the main engineering strategies. The results show that optimized surface modification significantly enhances charge carrier mobility, reduces recombination losses, and improves power conversion efficiency (PCE). These findings confirm the crucial role of surface engineering in advancing QDSC technology and provide a comprehensive framework for future research and development. In conclusion, this study contributes to the theoretical understanding and practical applications of QDSCs, highlighting the need for an integrated approach in surface engineering to achieve high-performance photovoltaic systems.